Aplicación de electroanalgesia transcutánea en perros domésticos, para la optimización en la recuperación de tratamientos post quirúrgicos (fracturas en extremidad posterior) en la clínica veterinaria dino sur del Distrito Metropolitano de Quito - Iza Chuquilla, Marco Polo (2015)
The study of the present investigation sought to determine the efficacy of transcutaneous electroanalgesia as post-surgical treatment in fractures of the hind limb in domestic dogs and establish a correct application technique, for this was taken into account the mode of function of the equipment, right place placement of the electrodes in addition to the frequency and duration of treatment. By comparing the results it was presumed that the transcutaneous application electroanalgesia improve the recovery rates of the variables flexion, extension and muscle tone of the hind limb. It was used as experimental model domestic dogs in an amount of 10 animals aged between six months and three years for which a consistent protocol of 250 microseconds (useg.)....